Peningkatan Kualitas Madrasah Yang Berfokus Pada Penguatan Program Vokasi - Nurul Mustabsyiroh; Raden Bambang Sumarsono; Ali Imron; Juharyanto Juharyanto (Universitas Negeri Malang, 2023)
Abstract: This study aims to describe the condition of the quality of Islamic education institutions after implementing doubletrack, and the strategy and implementation of the vocational program at MAN Kota Mojokerto. The research method is a qualitative approach to case study design with interview, observation, and documentation data collection techniques. The results of this research are that the Vocational Program is held on the basis of 1) the allocation of the distribution of graduates is mostly working; 2) the issuance of a decree stating that MAN in Mojokerto City has been transformed into MA Plus Skills; 3) Provision of grants from the Ministry of Religion for the purchase of supporting tools for the implementation of vocational programs. The implementation of the vocational program is included in the school intracurricular so that students who take part in the vocation are class X students except X-E5 and X-E6 and all class XI from the Science, Social Sciences and Religion majors using the moving class method every Monday and Friday. The strategies carried out are forming vocational teams, collaboration between teachers, rigorous selection of prospective vocational teachers, increasing teacher competency, and partner collaboration. Indicators of quality achievement from the implementation of the vocational program can be seen from the increase in student achievement, increase in existence, and increase in student skills. There are factors supporting quality improvement through the implementation of the vocational program including: 1) teacher collaboration, having professional teaching staff, student enthusiasm, support from student guardians, committees, and the existence of working partners. While the inhibiting factors are the lack of availability of facilities and infrastructure and the ups and downs of learning enthusiasm from students. Keywords: Enhancement; Quality; Madrasah; Program; Vocational Abstrak: Penelitian ini bertujuan untuk mendeskripsikan keadaan mutu lembaga pendidikan Islam setelah menerapkan doubletrack, dan strategi serta implementasi program vokasi di MAN Kota Mojokerto. Metode dalam riset pendekatan kualitatif rancangan studi kasus dengan teknik pengumpulan data wawancara, observasi, dan dokumentasi. Hasil riset ini adalah program vokasi diselenggarakan atas dasar (1) alokasi penyebaran lulusan sebagian besar bekerja; (2) pemberian SK bahwa MAN Kota Mojokerto bertranformasi menjadi MA Plus Keterampilan; (3) Pemberian dana hibah dari Kemenag untuk pembelian alat pendukung penyelenggaraan program vokasi. Pelaksanaan program vokasi dicantumkan dalam intrakulikuler sekolah sehingga peserta didik yang mengikuti vokasi yaitu siswa kelas X kecuali X-E5 dan X-E6 dan seluruh kelas XI baik dari jurusan IPA, IPS, dan Agama dengan metode moving class setiap hari senin dan jumat. Adapun strategi yang dilakukan yaitu pembentukan tim vokasi, kolaborasi antar guru, seleksi ketat calon guru vokasi, peningkatan kompetensi guru, dan kerja sama mitra. Indikator ketercapaian mutu dari pelaksanaan program vokasi dilihat dari peningkatan prestasi peserta didik, peningkatan eksistensi, dan peningkatan skill peserta didik. Terdapat faktor pendukung peningkatan mutu melalui penerapan program vokasi yaitu: (1) kolaborasi guru; (2) memiliki tenaga pendidik profesional; (3) antusiasme peserta didik; (4) dukungan dari wali murid dan komite; (6) adanya mitra kerja sama. Sedangkan faktor penghambatnya yaitu kurangnya ketersediaan sarana dan prasarana serta naik turunnya semangat belajar dari peserta didik. Kata kunci: Peningkatan; Kualitas; Madrasah; Program; Vokasi